CHARACTERISTICS OF RED DRAGON FRUIT SKIN DRY NOODLES (Hylocereus polyrhizus) WITH THE ADDITION OF TUNA FISH BONE MEAL - Eddwina Aidila Fitria; Hermalena, Leffy; Nadia Saputri; Nita Yessirita; Inawaty Sidabalok (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Noodles are one of the carbohydrate alternatives to rice. To get healthy noodles, you need additional vegetables or fruit. Dragon fruit skin is high in antioxidants that function to ward off free radicals. The addition of tuna bone meal as an additional nutritional value in the form of potassium and mineral. The purpose of this study was to determine the best characteristics of red dragon fruit skin dry noodles with the addition of tuna fish bone meal which were the best in making dry noodles that the panelists liked. This study used a Completely Randomized Design (CRD) with 5 treatment levels and 3 replications. Observational data were analyzed using Duncan’s New Multiple Range Test (DNMRT) at 1% level. The treatment in this study was the addition of tuna fish bone meal to dried red dragon fruit skin noodles (A=2%, B=4%, C=6%, D=8%, E=10%). The results showed that the addition of tuna bone meal had highly significant different, ash content, protein content, antioxidant test and calcium content. Based on the organoleptic test, dry noodles with treatment B (Addition of 4% tuna fish bone meal) were most preferred by the panelists and met the quality requirements of SNI No 8217-2015 with a composition of water content (11,47%), ash content (0,45%), protein content (16,24%), antioxidant test (34,38%) and calcium content (30,79%).